Comparison of the effect of two types of whole mushroom (Agaricus bisporus) powders on intestinal fermentation in rats - Kawakami, Sakura; Araki, Takahiro; Ohba, Kiyoshi; Sasaki, Keiko; Kamada, Takeo; Shimada, Ken-Ichiro; Han, Kyu-Ho; Fukushima, Michihiro (Bioscience, biotechnology, and biochemistry, 2016)
The effects of two types of mushroom (Agaricus bisporus; white, WM; brown, BM) powders on intestinal fermentation in rats were investigated in terms of the physical characteristics of animals and by bacterial and HPLC analyses of cecal contents. Short-chain fatty acid levels were found to be significantly higher in the WM group than in the BM and the control (CN) groups; coliform bacteria levels in the BM group were significantly lower than those in the CN group, with the WM group inducing an apparent but insignificant decrease in coliforms. Anaerobe levels in the WM group were significantly higher than those in the CN group and, compared with the CN group, the BM and WM groups exhibited significantly increased feces weight and cecum weight, respectively. These results indicate that the mushroom powders, and in particular the WM powder, have beneficial effects on the intestinal environment in rats. SCFA concentrations of cecal contents in rats fed a diet supplemented with mushroom powders (a) Acetic acid; (b) Butyric acid; (c) Propionic acid; (d) Total SCFA.